Ocean Commissions : Ocean Policy Review and Outlook. (U.S. Congressional Research., 2006)
Describes ocean policy reports and working documents prepared by the U.S. Commission on Ocean Policy and the Pew Charitable Trusts Oceans Commission, and reviews issues for Congress.